Student’s Mathematics Creative Thinking Skills in Terms of Logical Mathematical Intelligence (International Journal of Scientific Research and Management (IJSRM), 2017)
The objective of this study is to describe the skills of creative thinking in terms of logical mathematical intelligence, by qualitative approach. Instruments used were questionnaires, tests, documentation, and interviews. 54 students of class XI, MA Al-Misri were given a type of multiple intelligences questionnaire. 14 students who have logical mathematical intelligence predominant chosen as the subject of research. The first test was given to determine the logical mathematical intelligence, then analyzed. The analysis showed consecutively 12; 8; 5; 3; and 1 subject(s) who has the characteristics classify, compare, perform basic numerical operations, deductive and inductive reasoning, and hypothesis formation and testing. Next, each subject was chosen for each those characteristics. Open ended question was given for the second test to describe student’s creative thinking skills. Based on data analysis, it was found that the subjects with the characteristics classify, compare, perform basic numerical operations, deductive and inductive reasoning generally fulfill the components of creative thinking: problems sensitivity, fluency, flexibility and elaboration; and subject with characteristics of hypothesis formation and testing fulfill the four components later and novelty